A PHILOSOPHY-BASED LEARNING AS THE FOUNDATION FOR DEVELOPING CRITICAL THINKING SKILLS IN ELEMENTARY SCHOOLS - Raya Amanda Nur Islami; Yusuf Tri Herlambang (SOSIOEDUKASI, 2025)
Philosophy is often regarded as a discipline intended only for adults, even though thinking and questioning are natural instincts of children. In basic education, the Philosophy for Children (P4C) approach has the potential to serve as a fundamental framework for developing critical, reflective, and ethical thinking skills from an early age. This study aims to examine the implementation of philosophy in primary education and its relevance to character formation and the cultivation of children’s critical thinking abilities. The research employed a qualitative literature review by analyzing various national and international studies related to P4C. Thematic analysis was conducted to identify recurring patterns, key concepts, and the practical implications of applying philosophy in primary school contexts. The findings indicate that philosophy-based learning, through dialogic discussion and the Socratic method, enhances students’ critical thinking, empathy, communication, and moral awareness. In conclusion, philosophy education in elementary schools plays a crucial role in shaping students’ intellectual growth and reflective character. Therefore, integrating the P4C approach into the curriculum represents a strategic pathway toward more humanistic and contextually relevant education.